THE RETROGRADE LEFT ATRIAL TUMOUR EMBOLISM IN THE PATIENT WITH METASTATIC EXTREMITY CHONDROSARCOMA - Dogan, Emrah; Gül, Süha; Mouline Doğan, Marwa; Elibol, Cenk; Tapan, Utku; Oral Tapan, Özge (Journal of Ayub Medical College Abbottabad, 2022)
The malignancy-related coagulation and secondary pulmonary embolism are common in sarcomas, whereas tumour embolism and pulmonary venous embolism are extremely rare. It is crucial to distinguish thromboembolism and tumour embolism in cancer patients. Physio pathologic basis of these two entities is also different. Knowing the type of embolism changes medical management since tumour embolism is unresponsive to anticoagulant or thrombolytic treatments. In especially patients with disseminated metastases, venous tumour embolism may occur by reaching tumour cells to the pulmonary venous circulation. This case is the fifth retrograde left atrial cardiac tumour embolisms in the literature. CT images and also follow-up images were descriptive. We report a case of a 59-year-old female patient who underwent amputation caused by extremity chondrosarcoma accompanied by clinical and radiological findings. She had multiple lung metastases and also had a right inferior pulmonary venous embolism. The embolism reached the left atrium via retrograde way during the three-month follow-up. HU value was 77 in the first CT, while 81 HU after three months. Pecking and vascular enlargement were also observed in CT. Echocardiography showed an appearance of iso-echogenic heterogenic. CT findings and HU values were compatible with tumour embolism in light of the echocardiographic findings.